Giving Citizen Scientists a Chance: A Study of Volunteer-led Scientific Discovery - Miranda C. P. Straub (Citizen Science: Theory and Practice, 2016)
The discovery of a class of galaxies called Green Peas provides an example of scientific work done by volunteers. This unique situation arose out of a science crowdsourcing website called Galaxy Zoo. It gave the ability to investigate the research process used by the volunteers. The volunteers’ process was analyzed in terms of three models of scientific research and an iterative work model to show the path to this discovery. As has been illustrated in these models of science, the path was iterative, not predetermined, and driven by empirical data. This paper gives a narrative of the 11-month, volunteer-led discovery process of the Green Pea galaxies and the transition to the Galaxy Zoo science team’s involvement to analyze and report on a new class of galaxy. This study identified the cycles of the volunteers’ work and situated them in the proposed integrated model of the scientific research process to show that the volunteers engaged in meaningful scientific research.